KEPASTIAN HUKUM DALAM PELANGGARAN REGULASI PARQ KAMPUNG RUSIA DI UBUD BALI - Adnantara, Kadek Frediandrika (Universitas Tabanan, 2026)
Legal certainty is an important element in the enforcement of regulations, especially in the context of tourism development which often has the potential to violate spatial and environmental rules. The author discusses a case of regulatory violations committed by the Ubud PARQ, known as the